Capsaicin Ameliorates the Loosening of Mitochondria-Associated Endoplasmic Reticulum Membranes and Improves Cognitive Function in Rats With Chronic Cerebral Hypoperfusion - Ouyang, Mengqi; Zhang, Qi; Shu, Jiahui; Wang, Zhiqiang; Fan, Jin; Yu, Ke; Lei, Lei; Li, Yuxia; Wang, Qingsong (Frontiers in Cellular Neuroscience, 2022)
Based on accumulating evidence, vascular factors contribute to cognitive decline and dementia. Mitochondrial dysfunction is the core pathophysiological mechanism. Mitochondria-associated endoplasmic reticulum membranes (MAMs) are subcellular structures that physically and biologically connect mitochondria with the endoplasmic reticulum (ER) and regulate multiple functions ranging from calcium transfer to mitochondrial dynamics and bioenergetics. MAMs dysfunction has been speculated to be a key factor contributing to the pathogenesis of cognitive disorders and a new therapeutic target. However, the alteration of MAMs in vascular cognitive impairment remains to be revealed. Capsaicin, a specific agonist known to activated the transient receptor potential vanilloid type 1 (TRPV1), is involved in hippocampal synaptic plasticity and memory, but the detailed mechanism is still unclear. In this study, chronic cerebral hypoperfusion (CCH) model rats were created by bilateral common carotid artery occlusion (BCCAO), which is a widely used model to study vascular dementia. We observed that CCH rats showed obvious cognitive deficits, and ER-mitochondria contacts were loosener with lower expression of mitofusin2 (MFN2), a key protein connecting MAMs, in the hippocampal CA1 region, compared to the sham group. After capsaicin treatment for 12 weeks, we found that cognitive deficits induced by CCH were significantly alleviated and loosened ER-mitochondrial interactions were obviously improved. In conclusion, the findings of this study highlight that MAMs may contribute to the pathogenesis of cognitive impairment induced by CCH, and our new evidence that capsaicin improves cognitive function highlights a novel opportunity for drug discovery.